Development of a Mobile Application for Occupational Health and Safety Education in Vocational High Schools: A Case Study in Construction and Housing Engineering - Muhamad Faisal Aulia Nugraha; Roemintoyo Roemintoyo; Djono Djono; Hanan Al-Hakimi (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2024)
Students need to have a good understanding of occupational health and safety to avoid accidents during practical activities and in the workplace. To help with this, digital technology can be used to create learning materials and media that aid in achieving learning objectives. This study aimed to develop a mobile application that could be used as a learning resource during practical activities in workshops. The research was carried out at the Department of Construction and Housing Engineering in a Vocational High School in Surakarta, using the Alessi & Trollip research method. The development process consisted of three stages: Planning, Designing, and Development. The study employed various techniques, such as questionnaires, interviews, observation, and documentation, to collect research data. The study used interactive models to analyze qualitative data and descriptive statistics to analyze quantitative data. As a result, the learning resource created has a material suitability level of 90% and media suitability of 100%. User testing has shown positive results, with individual test scores averaging 90% and class test scores averaging 90.35%, which is rated as "very good." This study aims to provide an appropriate learning resource that addresses the identified problems.